2023
DOI: 10.7150/ijbs.80921
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP3 Regulates TMA7-mediated Autophagy and Cisplatin Resistance in Laryngeal Cancer via m6A RNA Methylation

Abstract: Translation machinery associated 7 homolog (TMA7) is closely related to proliferation-related diseases. However, the function and regulatory mechanism of TMA7 in laryngeal squamous cell carcinoma (LSCC) remain unclear. The present study aimed to investigate the effect of TMA7 on the occurrence and development of LSCC and to study the mechanism of TMA7. TMA7 is upregulated in LSCC tissues and associated with poor prognosis. After TMA7 downregulation, the autophagy level was increased, and the proliferation, mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Interestingly, after searching for any deregulated ribosome-related proteins besides Pelo, we found decreased levels of translation machinery associated 7 homolog (Tma7) and Endothelial differentiation-related factor 1(Edf1) in Hbs1l-deficient retina. Tma7 is a ubiquitously expressed protein that may inhibit autophagy by activating the PI3K/mTOR pathway (22), and Edf1 is reported to coordinate cellular responses to ribosome collisions (23, 24). In addition to rescuing the ribosomes stalled at the mRNA 3’ end (29), it remains to be elucidated if HBS1L/PELO may play a role in resolving collided ribosomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, after searching for any deregulated ribosome-related proteins besides Pelo, we found decreased levels of translation machinery associated 7 homolog (Tma7) and Endothelial differentiation-related factor 1(Edf1) in Hbs1l-deficient retina. Tma7 is a ubiquitously expressed protein that may inhibit autophagy by activating the PI3K/mTOR pathway (22), and Edf1 is reported to coordinate cellular responses to ribosome collisions (23, 24). In addition to rescuing the ribosomes stalled at the mRNA 3’ end (29), it remains to be elucidated if HBS1L/PELO may play a role in resolving collided ribosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, apart from impacting its partner protein Pelo, Hbs1l depletion is accompanied with reduced levels of translation machinery associated 7 homolog (TMA7), and Endothelial differentiation-related factor 1(EDF1) proteins. While TMA7 is closely related to cell proliferation and autophagy (22), EDF1 is known to coordinate cellular responses to ribosome collisions (23, 24), when ribosomes slow down or completely stall when they encounter obstacles on mRNAs. Together these findings suggest a broad impact by the loss of Hbsl1 and its associated transcriptional regulators on key proteins for photoreceptor health and visual function.…”
Section: Introductionmentioning
confidence: 99%
“…IGF2BP3 has been associated with gastric cancer progression, with high expression in four gastric cancer subtypes indicating its potential role in promoting cell growth and invasion ( Zhou et al, 2017 ). Yang et al (2023) reported the oncogenic and poor prognostic properties of IGF2BP3 and provided evidence that downregulation of IGF2BP3 leads to enhanced apoptosis. Moreover, IGF2BP3 has been linked to cisplatin resistance in laryngeal cancer ( Yang et al, 2023 ), providing further evidence for the potential role of IGF2BP3 in cisplatin-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… Yang et al (2023) reported the oncogenic and poor prognostic properties of IGF2BP3 and provided evidence that downregulation of IGF2BP3 leads to enhanced apoptosis. Moreover, IGF2BP3 has been linked to cisplatin resistance in laryngeal cancer ( Yang et al, 2023 ), providing further evidence for the potential role of IGF2BP3 in cisplatin-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Initial observations suggest that PI3K/AKT/mTOR signaling pathway plays an important role in the anti-autophagy effect [ 163 ]. IGF2BP3 promotes translation machinery associated 7 homolog (TMA7) mRNA stability and translation through recognition of the m 6 A site on the TMA7 3’-UTR, which in turn activates the PI3K/AKT/mTOR pathway and ultimately inhibits autophagy [ 164 ]. Conversely, activating transcription factor 4 (ATF4) negatively regulates the mTOR signaling pathway.…”
Section: The Indirect Regulatory Role Of M 6 a Met...mentioning
confidence: 99%